Gene Carriers and Transfection Systems Used in the Recombination of Dendritic Cells for Effective Cancer Immunotherapy. (20th December 2010) - Chen, Yu-Zhe; Yao, Xing-Lei; Tabata, Yasuhiko; Nakagawa, Shinsaku; Gao, Jian-Qing
Abstract : Dendritic cells (DCs) are the most potent antigen-presenting cells. They play a vital role in the initiation of immune response by presenting antigens to T cells and followed by induction of T-cell response. Reported research in animal studies indicated that vaccine immunity could be a promising alternative therapy for cancer patients. However, broad clinical utility has not been achieved yet, owing to the low transfection efficiency of DCs. Therefore, it is essential to improve the transfection efficiency of DC-based vaccination in immunotherapy. In several studies, DCs were genetically engineered by tumor-associated antigens or by immune molecules such as costimulatory molecules, cytokines, and chemokines. Encouraging results have been achieved in cancer treatment using various animal models. This paper describes the recent progress in gene delivery systems including viral vectors and nonviral carriers for DC-based genetically engineered vaccines. The reverse and three-dimensional transfection systems developed in DCs are also discussed.